Answer:
16
Step-by-step explanation:
3x=90 2x=50
And the last one is 40
Yuto is correct because he isolated the variable correctly and reversed the inequality symbol.
x < 3
Answer:
Step-by-step explanation:
(a+ b)² = a² + b² + 2ab
(2x + y)² = (2x)² + y² + 2*2x *y
= 4x² + y² + 4xy
(a- b)² = a² + b² - 2ab
(3x - 2y)² = (3x)² + (2y)² - 2*3x *2y
= 9x² + 4y² - 12xy
(a - b)(a +b) = a² - b²
(x - 4y(x + 4y) = x² - (4y)²
= x² - 16y²
(2x + y)² - (3x - 2y)² + (x - 4y)(x +4y)
= 4x² + y² + 4xy - (9x² + 4y² - 12xy) + x² - 16y²
= 4x² + y² + 4xy - 9x² - 4y² + 12xy + x² - 16y²
= 4x² - 9x² + x² + y² - 4y² - 16y²+ 4xy + 12xy
= -4x² - 19y² + 16xy